Immunohistochemical Distribution of Desmin and Vimentin in Bovine Spleen During Fetal Development - Topaloglu, Ugur; Akbalik, Mehmet Erdem; Ciga, Ayse Durmaz; Tekin, Abdullah Said (Selcuk Univ Press, 2026)
As one of the largest secondary lymphoid organs, the spleen, besides having a key role in filtering the blood, supporting the lymphocyte differentiation as well as maintaining immune system control, is the centre of haematopoiesis during the fetal period. Such essential cellular processes as cell maintenance, cell division and communication between cells are regulated by intermediate filaments. Among these filaments, vimentin and desmin play an important role in keeping mechanical strength and giving support to the cellular differentiation processes. Therefore, the presented study aims to find out how immunohistochemical distributions of vimentin and desmin are done in the fetal bovine spleen during gestation periods. In this study, from each gestational period, 10 spleen tissue samples were collected. Before serial sections were prepared and stained immunohistochemically, those spleen tissue samples were processed via basic histological procedures and embedded in paraffin. The study demonstrate that vimentin and desmin exhibited various levels of staining intensity within splenic cell during gestation. As a result, throughout prenatal development, vimentin and desmin proteins have been seen to have different dynamics with regards to the staining intensity and distribution in the spleen. With this study, it was concluded that proteins from both might have a crucial role in giving contribution to the essential biological processes, like cell proliferation and differentiation, the structural organization of the splenic stroma, blood cell formation, and the regulation of immune responses.
Keywords: Bovine fetus; Desmin; Immunohistochemistry; Spleen; Vimentin